Inhibitory effects of salviae miltiorrhizae radix (danshen) and puerariae lobatae radix (gegen) in carbachol-induced rat detrusor smooth muscle contractility - Teong, Ivy Wen Jia (2014)
Both danshen (D) and gegen (G) have proven relaxant effects on vascular smooth muscle, thus their potential bladder inhibitory effects have impending interests in urology. The aim of this study was to demonstrate the novel effects of D and G on detrusor smooth muscle contractility. Urothelium-intact (+UE) and urothelium-denuded (–UE) detrusor strips were isolated from the rat. Isometric tension was measured using a myograph system. Carbachol (CCh) was used to pre-contract the detrusor strips prior to stepwise relaxation by adding extracts of D, G, and a DG (7:3) formulation. Tonic relaxation level and phasic contractile activity under the herbal treatments were analyzed. There was no difference in the herbal effects between +UE and –UE strips. D alone induced a much smaller relaxation than G alone or DG. G alone also suppressed phasic amplitude but not phasic frequency while DG suppressed both parameters. D and G acted synergistically to yield the observed effects on detrusor smooth muscle. The findings showed that the DG formulation were able to relax the detrusor as well as suppress phasic contractions, both actions important in maintaining normal bladder filling and urine storage processes. Hence DG may have new application in the management of bladder disorders.